The Role of Green Finance (Green Sukuk and Green Bonds) In Sustainable Development: Selected Experiences With A Special Reference To Iraq - Haqi Tomas (Indonesian Journal Publisher, 2025)
The research population to reveal the role of green financing (green sukuk and green bonds) in sustainable development, as the world population is expected to reach 9 billion by 2050, This population increase requires the availability of food, water, and energy, and undoubtedly the current growth patterns are inefficient and insufficient for such a population, as they still rely on traditional economic growth methods despite many countries adopting sustainable development. The proper path today is to move towards green growth and the transition to a green economy, so that growth becomes inclusive and environmentally friendly, efficient in the use of natural resources, and meets the needs of all citizens. The research aims to identify green finance instruments (green sukuk and green bonds) by defining them, their importance, characteristics and key principles. The research also aims to study the experiences of some countries in the field of green finance and the use of its instruments to transition towards a green economy, including China and the United Arab Emirates. Furthermore, the research aims to study Iraq's direction towards transitioning to a green economy and sustainable development, highlighting the key steps it has started on this path, and to determine a future vision for transitioning to a green economy in Iraq, following the example of other countries worldwide. The research has reached a set of conclusions and recommendations related to the study.